Purpura with regular shape in an adolescent: Beware of dermatitis artefacta - Chen, Yuhao; Li, Lin; Lu, Jing (Frontiers in Pediatrics, 2022)
Background: Purpura is common in pediatric patients, mostly diagnosed as IgA-related vasculitis (Henoch-Schonlein purpura), idiopathic thrombocytopenic purpura (ITP), thrombotic thrombocytopenic purpura (TTP) and so on. But in some cases, for example, cases with dermatitis artefacta, it could puzzle a physician or pediatrician for a long time, with great challenges in diagnosis. Case Presentation: We present the case of a 13-year-old boy with recurrent painful purpura on both upper limbs, the physical exam was unremarkable, except for right blepharoptosis and scars for burns. Diagnostic tests were normal. Through repeated communication and finally diagnosed as dermatitis artefacta, companied by underlying psychological problems. Conclusions: Before the diagnosis of dermatitis artefacta was made, we spent a lot of money and effort on diagnosing. Therefore, in order to make the diagnosis as soon as possible and save unnecessary medical investment, we proposed a rapid diagnosis process for children on purpura of dermatitis artefacta.